Perancangan Perancangan Ui / Ux Untuk Aplikasi Bimbingan Belajar (BIJAR) Menggunakan Figma Model Design thinking - Rahmadani, Renita (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2024)
This study aims to test UI / UX design in the BIJAR application using figma model design thinking. In this study, the author designed an application system for of tutoring in Pekanbaru city regarding mapping the location of tutoring places. The results of this study show that UI / UX design on the BIJAR application using figma model design thinking for mapping the location of tutoring places in Pekanbaru city can help users, especially students. Tutoring serves to orient the students to the school, help the students to plan their education in high school, and help the students to get to know their respective interests and abilities, orienting the students towards the world of work, After designing a User Interface , it is tested using the SUS (System Usability Scale) and scores 80 points on the B grade scale, making the User Interface design suitable for application development.